Bringing soils back to life: a conversation with Deborah Bossio - CGIAR Research Program on Water, Land and Ecosystems (2015)
On this episode of Thrive podcast, we sit down with of Dr. Deborah Bossio, the Area Director of Soils Research at the CGIAR International Center for Tropical Agriculture. Bossio has spent the last 20 years working at the nexus between soil and social sciences. Based in Kenya, she jointly leads two programs within the WLE network. One works on regenerating degraded ecosystems, the other on ecosystems services and resilience, a core theme in WLE.